"The Story of the Kowalski Family" and Quarter L. Memory Messages on the Screen - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article is devoted to two films by the independent operator, director and producer Arkadiusz Gołębiewski: The Story of the Kowalski Family (Historia Kowalskich), which raises the subject of the Holocaust, and Quarter L (Kwatera Ł), which deals with Stalin’s crimes in Poland. They are interpreted not as historical works, but as films about memory and - in the case of the latter - memory in statu nascendi. Their involvement in political and historical polemics and their relationship to the vision of history supported by the Polish State are analyzed.